Correction of anemia using an iron supplement with a hepcidin-independent absorption mechanism in patients with chronic heart failure with preserved left ventricular ejection fraction - A. A. Gurkina; N. I. Stuklov; V. A. Kokorin; R. R. Gimadiev; N. V. Varekha (Рациональная фармакотерапия в кардиологии, 2025)
Aim. To characterize anaemia in chronic heart failure (CHF) with preserved left ventricular ejection fraction (CHFpEF) and evaluate the effectiveness of an iron supplement with a hepcidin- independent absorption mechanism.   Material and methods. An uncontrolled study included 30 patients with CHFpEF NYHA class I-III and anaemia. Patients received "standard therapy" for CHF in combination with sucrosomial iron (60 mg/day orally) for three months. Treatment response was assessed via clinical blood test, iron metabolism parameters, inflammatory markers, and functional tests at baseline and three months post-treatment.   Results. Anaemia in CHFpEF corresponds to anaemia of chronic disease with elevated hepcidin content, 219 (149-553) ng/mL occurs with impaired absorption and metabolism of iron and the development of iron deficiency. Hemoglobin levelincreased from 115 (98-117) g/L to 120 (103-133) g/L, p = 0.01, red blood cell count increased from 3.6 (3.5-4.1) × 1012/L to 4 (3.7-5.3) × 1012/L, p = 0.05, and serum ferritin increased from 106 (40-181) μg/L to 117 (83-166) μg/L, p = 0.04. N-terminal natriuretic propeptide (NT-proBNP) level decreased from 374 (330-443) ng/mL to 236 (128-349) ng/mL, p = 0.004. After treatment, exercise tolerance exercise tolerance improved: 6-minute walk test distance increased from 343.1 ± 100 m to 397±73 m (p = 0.01). Quality of life (QoL) level increased and was determined by the clinical status assessment scale (CAS), p = 0.01 and by the Minnesota Health Failure Questionnaire (MHFLQ), p = 0.002.   Conclusion. Adding oral hepcidin- independent iron to standard HFpEF therapy in patients with CHFpEF and anaemia significantly increased hemoglobin and serum ferritin levels, exercise tolerance, and QoL scores while reducing NT-proBNP levels and NYHA functional class after three months.